Trend 1995 - 2012. Statistics Canada. CANSIM: Energy - Crude Oil and Natural Gas | Country: Canada | Province: Newfoundland and Labrador | Table: Supply and demand of natural gas liquids | Variable: Gas plant natural gas liquids (NGL's), Megalitres, Agriculture | Units: Megalitres, 1995-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-077. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Energy - Crude Oil and Natural Gas | Country: Canada | Province: Newfoundland and Labrador | Table: Supply and demand of natural gas liquids | Variable: Gas plant natural gas liquids (NGL's), Megalitres, Agriculture | Units: Megalitres, 1995-2012. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-077. Dataset: Presents statistics on the production and extraction of crude oil in Canada, including production statistics, final destination of crude oil, and the surplus and disposition of crude oil. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Energy Resources and Industries Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Natural Gas, Natural Gas Production, Energy Supply, Crude Oil, Crude Oil Production